Integrating behavior and intention regarding mammography by respondents in the 1990 National Health Interview Survey of Health Promotion and Disease Prevention. - Rakowski, W (1993)
Achieving and maintaining high rates of screening mammography are major public health priorities. This report examines data from the 1990 National Health Interview Survey of Health Promotion and Disease Prevention on the utilization of mammography among women ages 40-75. Results show that progress is being made in some areas--57.7 percent of women "ever had" a mammogram; 50.3 percent, in previous 2 years. However, those not having repeated regular screening appear to be a sizable proportion. Only 28.6 percent of women ages 40-75 had been both screened on the recommended age-specific schedule and expressed an intention to continue screening; another 29.2 percent indicated no intention to have a mammogram in the near future. Income, clinical breast examination, and Pap (Papanicolaou's) test, having no regular source of care, region of the country and residential variables, smoking status, not exercising, not knowing how to do breast self-examination, and race were among the variables having the strongest associations with mammography status. Several groups in the population therefore remain at risk of not receiving regular screening. The combination of mammography status to date and future intention to have the examination provides an important perspective on efforts to reach public health screening objectives and appears to provide a strategy for targeting interventions.